Benefiting others and self: Production of vitamins in plants. Issue 1 (27th January 2021) - Li, Yufei; Yang, Chenkun; Ahmad, Hasan; Maher, Mohamed; Fang, Chuanying; Luo, Jie
Abstract: Vitamins maintain growth and development in humans, animals, and plants. Because plants serve as essential producers of vitamins, increasing the vitamin contents in plants has become a goal of crop breeding worldwide. Here, we begin with a summary of the functions of vitamins. We then review the achievements to date in elucidating the molecular mechanisms underlying how vitamins are synthesized, transported, and regulated in plants. We also stress the exploration of variation in vitamins by the use of forward genetic approaches, such as quantitative trait locus mapping and genome‐wide association studies. Overall, we conclude that exploring the diversity of vitamins could provide new insights into plant metabolism and crop breeding. Abstract : Vitamins maintain growth and development in humans, animals, and plants. In this review, we summarize recent progress on vitamin synthesis, transport, regulation, and functions in plants, as well as discussing the strategies for research on plant vitamins and prospects for application of vitamins in crop breeding.